Who benefits from quality competition in health care? A theory and a laboratory experiment on the relevance of patient characteristics - Brosig-Koch, Jeannette; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We study how competition between physicians affects the provision of medical care. In our theoretical model, physicians are faced with a heterogeneous patient population, in which patients systematically vary with regard to both their responsiveness to the provided quality of care and their state of health. We test the behavioral predictions derived from this model in a controlled laboratory experiment. In line with the model, we observe that competition significantly improves patient benefits as long as patients are able to respond to the quality provided. For those patients, who are not able to choose a physician, competition even decreases the patient benefit compared to a situation without competition. This decrease is in contrast to our theoretical prediction implying no change in benefits for passive patients. Deviations from patient-optimal treatment are highest for passive patients in need of a low quantity of medical services. With repetition, both, the positive effects of competition for active patients as well as the negative effects of competition for passive patients become more pronounced. Our results imply that competition can not only improve but also worsen patient outcome and that patients’ responsiveness to quality is decisive.
Keywords: physician competition; patient characteristics; heterogeneity in quality responses; fee-for-service; laboratory experiment

Price Regulation, Quality Competition and Location Choice with Costly Relocation - Hehenkamp, Burkhard; Kaarbøe, Oddvar M.
We consider a model where for-profit providers compete in quality in a price-regulated market that has been opened to competition, and where the incumbent is located at the center of the market, facing high costs of relocation. The model is relevant in markets such as public health care, education and schooling, or postal services. We find that, when the regulated price is low or intermediate, the entrant strategically locates towards the corner of the market to keep the incumbent at the low monopoly quality level. For a high price, the entrant locates at the corner of the market and both providers implement higher quality compared to a monopoly. In any case, the entrant implements higher quality than the incumbent provider. Social welfare is always higher in a duopoly if the cost of quality is low. For higher cost levels welfare is non-monotonic in the price and it can be optimal to the regulator not to use its entire budget. Therefore, the welfare effect of entry depends on the price and the size of the entry cost, and the regulator should condition the decision to allow entry on an assessment of the entry cost.
Keywords: Quality competition; Price regulation; Location choice; Product differentiation

The Market for Services: Incentives, Algorithms, Implementation - Haake, Claus-Jochen; Hehenkamp, Burkhard; Polevoy, Gleb (On-The-Fly Computing -- Individualized IT-services in dynamic markets)

The Impact of Product Differentiation on Retail Bundling in a Vertical Market - Endres-Fröhlich, Angelika Elfriede; Hehenkamp, Burkhard; Heinzel, Joachim
We study the effects of product differentiation on the bundling incentives of a two-product retailer. Two monopolistic manufacturers each produce a differentiated good. One sells it to both retailers, while the other only supplies a single retailer. Retailers compete in prices. Retail bundling is profitable when the goods are close substitutes. Only then is competition so intense that the retailer uses bundling to relax competition both within and across product markets, despite an aggravation of the double marginalization problem. Our asymmetric market structure arises endogenously for the case of close substitutes. In this case, bundling reduces social welfare.
Keywords: Retail bundling; upstream market power; double marginalization; product differentiation

Projekt Art-D Grids: Nachhaltige und stabile Microgrids in Afrika - eine Plattform für Forschung und Lehre für die Entwicklung - Krauter, Stefan; Böcker, Joachim; Freitag, Christine; Hehenkamp, Burkhard; Hilleringmann, Ulrich; Temmen, Katrin; Klaus, Tobias; Rohrer, Nicolaus; Lehmann, Sven (Tagungsband des 36. PV-Symposiums, 18.-26 Mai 2021)
Keywords: Art-D; Afrika; Resilienz; Resilience; Grid stability; robustness; microgrids

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarbøe, Odvar M. (Journal of Economic Behavior & Organization)
Many countries have opened their health care markets to private for-profit providers, aiming to promote quality and choice for patients. The prices are regulated and providers compete in location and quality. We show that whereas opening a public hospital market typically raises quality, the private provider strategically locates towards the corner of the market to avoid costly quality competition. Social welfare depends on the size of the regulator's budget and on the altruism of the public provider. If the budget is large, high quality results and welfare is highest in a duopoly whenever entry is optimal. If the budget is small, quality levels in a duopoly mirror the quality level in a monopoly. It can be optimal for the regulator not to use the full budget.

Evolutionary equilibrium in contests with stochastic participation: Entry, effort and overdissipation - Gu, Yiquan; Hehenkamp, Burkhard; Leininger, Wolfgang (Journal of Economic Behavior & Organization)
This paper examines the evolutionary stability of behaviour in contests where players’ participation can be stochastic. We find, for exogenously given participation probabilities, players exert more effort under the concept of a finite-population evolutionarily stable strategy (FPESS) than under Nash equilibrium (NE). We show that there is ex-ante overdissipation under FPESS for sufficiently large participation probabilities, if, and only if, the impact function is convex. With costly endogenous entry, players enter the contest with a higher probability and exert more effort under FPESS than under NE. Importantly, under endogenous entry, overdissipation can occur for all (Tullock) contest success functions, in particular those with concave impact functions.

The effects of competition on medical service provision - Brosig-Koch, Janet; Hehenkamp, Burkhard; Kokot, Johanna (Health Economics)
We explore how competition between physicians affects medical service provision. Previous research has shown that, without competition, physicians deviate from patient‐optimal treatment under payment systems like capitation and fee‐for‐service. Although competition might reduce these distortions, physicians usually interact with each other repeatedly over time and only a fraction of patients switches providers at all. Both patterns might prevent competition to work in the desired direction. To analyze the behavioral effects of competition, we develop a theoretical benchmark that is then tested in a controlled laboratory experiment. Experimental conditions vary physician payment and patient characteristics. Real patients benefit from provision decisions made in the experiment. Our results reveal that, in line with the theoretical prediction, introducing competition can reduce overprovision and underprovision, respectively. The observed effects depend on patient characteristics and the payment system, though. Tacit collusion is observed and particularly pronounced with fee‐for‐service payment, but it appears to be less frequent than in related experimental research on price competition.

Location Choice and Quality Competition in Mixed Hospital Markets - Hehenkamp, Burkhard; Kaarboe, Oddvar

Evolutionary Equilibrium in Stochastic Contests - Entry, Effort, and Overdissipation - Gu, Yiguan; Hehenkamp, Burkhard; Leininger, Wolfgang

Too Much of a Good Thing? Welfare Consequences of Market Transparency - Gu, Yiquan; Hehenkamp, Burkhard (Journal of Institutional and Theoretical Economics JITE)
This paper studies welfare consequences of consumer-side market transparency with endogenous entry of firms. Different from most studies, we consider the unique symmetric entry equilibrium, which is in mixed strategies. We identify two effects of market transparency on welfare: a competition effect and a novel market-structure effect. We show, surprisingly, that for almost all demand functions the negative market-structure effect eventually dominates the positive competition effect as the market becomes increasingly transparent. Consumer-side market transparency can therefore be socially excessive even without collusion. The only exception among commonly used demand functions is the set of constant demand functions.

Paying for Performance in Hospitals - Hehenkamp, Burkhard; Kaarboe, Oddvar (Economic Analysis and Policy)

Survival at the center—the stability of minimum differentiation - Hehenkamp, Burkhard; Wambach, Achim (Journal of Economic Behavior & Organization)

On the equivalence of Nash and evolutionary equilibrium in finite populations - Hehenkamp, Burkhard; Possajennikov, Alex; Guse, Tobias (Journal of Economic Behavior & Organization)

Imitators and optimizers in a changing environment - Hehenkamp, Burkhard; Kaarbøe, Oddvar M. (Journal of Economic Dynamics and Control)

The strategic advantage of interdependent preferences in rent-seeking contests - Guse, T.; Hehenkamp, Burkhard (Public Choice)

When Should the Talented Receive Weaker Incentives? Peer Pressure in Teams - Hehenkamp, Burkhard; Kaarboe, Oddvar (FinanzArchiv: Public Finance Analysis)

Evolutionary equilibrium in Tullock contests: spite and overdissipation - Hehenkamp, Burkhard; Leininger, W.; Possajennikov, A. (European Journal of Political Economy)

Equilibrium Selection in the Two-Population KMR Model - Hehenkamp, Burkhard (International Game Theory Review)

Sluggish Consumers: An Evolutionary Solution to the Bertrand Paradox - Hehenkamp, Burkhard (Games and Economic Behavior)

A note on evolutionary stability of Bertrand equilibrium - Hehenkamp, Burkhard; Leininger, Wolfgang (Journal of Evolutionary Economics)

Economic natural selection in Bertrand and Cournot settings - Hehenkamp, Burkhard; Qin, Cheng-Zhong; Stuart, Charles (Journal of Evolutionary Economics)